Potential of Solar PV Electrical Energy with a Capacity of 2x550 Wp on Cadet Training Ships - Amrillah, Muhamad Fahmi; Yulianto, Andri; Widjatmoko, Eko Nugroho; Yudha, Dimas Pratama; Firzatullah, R Muhammad (TELKA - Telekomunikasi Elektronika Komputasi dan Kontrol, 2025)
The development of the utilization of electrical energy sourced from the sun is currently experiencing very rapid development. The use of electrical energy sourced from the sun is not only used for industrial generation, currently the transportation industry also utilizes electrical energy sourced from the sun for propulsion and domestic needs. This study discusses the potential of electrical energy that can be generated by solar PV with a capacity of 2x550 Wp which will be implemented on cadet training ships. Solar irradiance is the most important component for the process of generating electrical energy, where later the irradiance value will become electrical energy using solar PV media. The irradiance value is obtained from a web application called solarglobalatlas which already has big data about the irradiation value in various places. This study took irradiation values in the coordinates area -2.953161°, 104.886022° (-02°57'11", 104°53'10") South Sumatra. The data was taken for 12 months to ensure that the data radiation experienced two seasons according to the characteristics of the area. The best irradiance values occur at 11.00 am – 01.00 pm. The results of the discussion show that the annual electrical energy that can be generated by solar PV with a capacity of 2x550 Wp using the monocrystalline PV type is 1,338.2 kWh with the largest electricity production peak occurring in August of 114.4 kWh. Meanwhile, the smallest production of electrical energy occurred in February at 87.2 kWh.